Catalytic branching cascades in diversity oriented synthesis - Bansode, Avinash H.; Chimala, Prathyusha; Patil, Nitin T. (ChemCatChem, 2017)
Diversity oriented synthesis (DOS) aims to generate small molecules with great structural diversity in an efficient manner. Recent years have witnessed significant achievements in the field, which help to validate the usefulness of DOS as a tool for the discovery of novel, biologically interesting small molecules. Catalytic branching cascades have emerged as a promising strategy because of their potential to transform a common type of substrate into diverse and distinct molecular frameworks. The details of the concept are presented herein.